Pendidikan Seksual Perspektif Hukum Keluarga: - Putri Ulul Azmi; Pratiwi Uly Romadhoni (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Sexual violence against minors has become one of the discussions of social problems at the international level. As proof, there is an increasing number of cases of violence against children in various regions in Indonesia. In this case, minors can be targeted by victims and perpetrators of immoral acts. Parents and family are key indicators that play an important role in family safety and honor. Sexual education from an early age needs to be done by the closest people, especially parents, family, teachers, and others. Therefore, the author raises a topic related to the role of parents in sexual education from the perspective of Islamic family law. This research is to provide an understanding of the importance of the role of parents in educating and teaching sexual education to children from an early age. In addition, it also discusses and analyzes sanctions that will be given in a case of sexual violence that occurs in minors. The method used in this research is literature studies (library research).The results of this study explained that Islam views sexual education as one of the most important aspects of life. It is because sexual education is closely related to religious education, such as morals, creeds, and worship. Sexual violence can occur due to two factors, namely internal and external factors. Violence against children can be categorized into psychological violence, physical violence, sexual violence, and social violence. In addition, there are several factors that support sexual education for children and adolescents in Islam, for example, instilling shyness, getting used to lowering one's gaze, applying social manners and showing Islamic looks, and so on. Sanctions that are suitable for handling cases of sexual violence against minors are Restorative Justice. Keywords: Sexual Violence, Minors, Early Childhood Sexual Education, Islamic Family Law